(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The integration of wind farms with transmission networks exhibits several problems. The sub-synchronous resonance (SSR) plays a vital role in those issues, and it must be reduced. Two effective flexible ac transmission system (FACTS) based voltage control devices, namely static synchronous series compensator (SSSC) and static compensator (STATCOM) are proposed in this paper to mitigate the SSR. Detailed eigenvalue analysis was conducted to prove the successful mitigation of SSR by two controllers in a series of compensated wind farms. To find the dominant control scheme, the eigenvalues of the proposed controllers are compared with PSCAD/EMTDC simulations. Finally, a comparison study is carried out between the two proposed SSR controllers. Further, the fuzzy logic control based on STATCOM and SSSC is also developed to enhance the stability margin of the wind turbine. The results have been validated with the IEEE 1st SSR benchmark system. From the results, it is proven that Fuzzy Logic Controller (FLC) based SSSC exhibits better performance than STATCOM.